Implementation of Small Group Discussion in Teaching Writing Descriptive Text: Senior High School Teacher’s Experience - Zahrah, Shofura; Miftakh, Fauzi; Kamil, Acep Bahrum (IKIP Siliwangi, 2025)
Small group discussion is a student-centered method that is effective in increasing students’ activeness, for example, in learning writing. This research aims to explore teacher’s experience in implementing small group discussions when teaching writing descriptive text. Through a descriptive qualitative approach, data was collected by interviewing the teacher was teaching writing descriptive text using small group discussion in senior high school grade 11th. The result shows the teacher’s experience in implementing small group discussions in teaching writing descriptive is good, and her opinion about this method is that small group discussions are proven effective when implemented in class and can increase students’ activeness, creativity, and confidence. Moreover, small group discussions also have disadvantages; one is that students rely on their friends in the group. So, the solution that the teacher can do is to make students’ assessment diagnostic to know better and understand the potential skills that students have.